Innovative Approach and Model for Arabic Curriculum Development in The Society 5.0 Era - Sulaeman, Islamiyah (Kitaba, 2023)
This study aims to describe approaches and models of Arabic curriculum development relevant to the era of Society 5.0. This research uses a qualitative-descriptive system with a literature study method. The results of this study found that the use of the STEAM approach and SAR (Systematic Action Research) development model are relevant to be used in developing the Arabic curriculum in the era of Society 5.0. Integrating an innovative Arabic curriculum through the STEAM approach and the SAR development model can actively motivate students, increase their interest in learning, and produce skills relevant to the demands of an increasingly technologically advanced society. These findings contribute to developing an Arabic curriculum that is more relevant to the needs of learners in the era of Society 5.0. This STEAM-based SAR model can guide educators in facing the challenges and opportunities that exist in developing Arabic learning that is adaptive and responsive to social and technological changes